Filsafat dan Ilmu Pengetahuan: Literature Review - Sarjayadi, Sarjayadi; Fitrisia, Azmi; Ofianto, Ofianto (LPPM Universitas Ekasakti, 2023)
This article is a comprehensive analysis that explores the correlation between philosophy and science. The intriguing argument has revolved around the intimate connection between philosophy and science, despite their divergent approaches and objectives. This article aims to explore the role of philosophy in enhancing comprehension and advancement of science. This literature study examines the perspectives of some renowned philosophers on the subject of science. This article explores logical positivism, a philosophical school of thought that places great emphasis on the significance of scientific techniques and empirical verification in acquiring true knowledge. Additionally, the text delves into Popper's falsificationist ideology, highlighting the significance of conducting tests to validate theories and dismissing unverified assertions. This literature study aims to go into a more profound comprehension of the connections and contributions of philosophy to science. By gaining a deeper comprehension of these connections, we can foster more effective cooperation between philosophers and scientists, leading to a more comprehensive and enduring approach to knowledge advancement.